INVESTIGATING THE EFFECTIVENESS OF DISTRIBUTED ELECTRIC PROPULSION FOR AIRCRAFTS - Arystanbekov, Chingiz (School of Engineering and Digital Sciences, 2023)
This work presents an experimental evaluation of the performance of a two-propeller propulsion system. Various propeller placement configurations relative to the trailing edge were investigated. The aerodynamic performance of a wing with two propellers was compared to that of a baseline wing using a NACA 2418 airfoil. The experimental work was conducted in a 600 mm wide AF1600s subsonic wind tunnel at Re = 91,000. The results of the first experiment indicate that propeller placement plays a crucial role in determining the vertical force generated by a model aircraft, especially at different throttle settings. Specifically, the configuration with propellers located at x/c = 1/3 and y/c = 0.71 yielded the highest vertical force at 20% throttle, while the configuration with propellers closer to the trailing edge (x/c = 1/9) resulted in the greatest vertical force at 40% throttle. The net vertical force acting on the wing was found to be increased by 15.2% and 34.12% at 20% and 40% throttle, respectively, compared to the clear wing. To isolate the impact of the propellers on the wing the thrust generated by the propellers was measured and later accounted for in the analysis. This approach enabled the evaluation the aero-coupling effect of the propellers on the wing. The findings of the first experiment were inconclusive, as the lift coefficient initially increased up to an angle of attack (AOA) of 10°, then slightly dropped before increasing again. This behavior may suggest a stall delay, but additional research using particle image velocimetry (PIV) is needed to confirm this hypothesis. To achieve steady level characteristics, the second experiment was performed by adjusting the throttle settings and free stream velocity at various angles of attack ranging from 2° to 20°. The objective was to ensure that the net vertical and horizontal forces were equal to zero. The findings indicated that the minimum required throttle and free stream velocity were 26.5% and 11.42 m/s, respectively, which were observed at an angle of attack of 10°. The findings of this study highlight the importance of propeller placement in determining the net forces acting on a wing. Firstly, placing the propellers too close to the wing may result in a degradation of overall performance. Secondly, positioning the propellers vertically above the trailing edge is effective at smaller angles of attack, as it accelerates the flow above the wing, contributing to the lift. Furthermore, the research indicates that adjustments in throttle settings and free stream velocity can help achieve steady level flight characteristics.
Keywords: type of access: open access; aircrafts; electric propulsion